Multiple sessions of low-frequency repetitive transcranial magnetic stimulation in focal hand dystonia: clinical and physiological effects - Kimberley, Teresa Jacobson (Restor Neurol Neurosci, 2013)
PURPOSE: The ability of low-frequency repetitive transcranial magnetic stimulation (rTMS) to enhance intracortical inhibition has motivated its use as a potential therapeutic intervention in focal hand dystonia (FHD). In this preliminary investigation, we assessed the physiologic and behavioral effects of multiple sessions of rTMS in FHD. METHODS: 12 patients with FHD underwent five daily-sessions of 1Hz rTMS to contralateral dorsal premotor cortex (dPMC). Patients held a pencil and made movements that did not elicit dystonic symptoms during rTMS. We hypothesized that an active but non-dystonic motor state would increase beneficial effects of rTMS. Five additional patients received sham-rTMS protocol. The area under curve (AUC) of the motor evoked potentials and the cortical silent period (CSP) were measured to assess changes in corticospinal excitability and intracortical inhibition, respectively. Behavioral measures included pen force and velocity during handwriting and subjective report. RESULTS: Multiple-session rTMS strengthened intracortical inhibition causing a prolongation of CSP after 3 days of intervention and pen force was reduced at day 1 and 5, leaving other measures unchanged. 68% of patients self-reported as ‘responders’ at day 5, and 58% at follow-up. Age predicted responders. CONCLUSIONS: A strong therapeutic potential of this rTMS paradigm in FHD was not supported but findings warrant further investigation.